Emotional cascade theory and non-suicidal self-injury: the importance of imagery and positive affect - Hasking, Penelope; Di Simplicio, M.; McEvoy, Peter; Rees, Clare (Routledge, 2017)
Grounded in Emotional Cascade Theory, we explored whether rumination and multisensory imagery-based cognitions moderated the relationships between affect and both odds of non-suicidal self-injury (NSSI), and frequency of the behaviour. A sample of 393 university students completed self-report questionnaires assessing the constructs of interest. Contrary to expectations, rumination did not emerge as a significant moderator of the affect-NSSI relationship. However, the relationship between affect and frequency of NSSI was moderated by the use of imagery. Further, the relationship between negative affect and NSSI was moderated by positive affect, underscoring the need to consider both negative and positive affect in models of NSSI. Most youth who self-injured reported thinking in images while the urge to self-injure was strong, with 53% thinking in images at least half the time. Future work is needed to explore how positive and negative affect work in concert to govern NSSI, and how imagery might either exacerbate or reduce risk of NSSI.